Предмет: Математика,
автор: ronaldo715
f(x)=sinx+cosx
f(x)=3sinx-4cosx
Ответы
Автор ответа:
0
1)f(x)= sinx-cosx=корень(2)*(1/корень(2)*sinx-1/корень(2)*cosx)==корень(2)*(cos (pi/4)*sinx-sin (pi/4)*cos x)=корень(2)*sin(x-pi/4)2) f(x)=03sinx-4cosx=0.
Всё это разделить на cosx не равно нулю, получается:3tgx-4=03tgx=4tgx=4/3x=arctg4/3 +пи*n? где n принадлежит Z.
Всё это разделить на cosx не равно нулю, получается:3tgx-4=03tgx=4tgx=4/3x=arctg4/3 +пи*n? где n принадлежит Z.
Похожие вопросы
Предмет: Информатика,
автор: igorekpolovnik
Предмет: История,
автор: Аноним
Предмет: Физика,
автор: s1ple4
Предмет: Математика,
автор: ДанаДана12345